The son of Neptune - Riordan, Rick. (New York : Disney/Hyperion Books, 2013)
Demigod Percy Jackson, still with no memory, and his new friends from Camp Jupiter, Hazel and Frank, go on a quest to free Death, but their bigger task is to unite the Greek and Roman camps so that the Prophecy of Seven can be fulfilled.
School Library Journal
Wilson's Children
Wilson's Junior High School
Booklist, November 2011
Horn Book, April 2012
Kirkus Review, November 2011
Keywords: Camps -- Juvenile fiction; Gaia (Greek deity) -- Juvenile fiction; Hera (Greek deity) -- Juvenile fiction; Jackson, Percy (Fictitious character) -- Juvenile fiction; Monsters -- Juvenile fiction; Mythology, Greek -- Juvenile fiction; Mythology, Roman -- Juvenile fiction; Prophecies -- Juvenile fiction; Camps -- Fiction; Fantasy; Gaia (Greek deity) -- Fiction; Hera (Greek deity) -- Fiction; Jackson, Percy (Fictitious character) -- Fiction; Monsters -- Fiction; Mythology, Greek -- Fiction; Mythology, Roman -- Fiction; Prophecies -- Fiction; Camps -- Fiction; Gaia (Greek deity) -- Fiction; Greek mythology -- Fiction; Hera (Greek deity) -- Fiction; Jackson, Percy (Fictional character) -- Fiction; Monsters -- Fiction; Prophecies -- Fiction; Roman mythology -- Fiction; Fantastic fiction; Fantastic fiction